Importancia del análisis químico del suelo para evitar deficiencias o excesos de fertilizantes en el cultivo de maíz - Zamora Zambrano, Ronald Jacinto (2024)
This study highlights the importance of soil chemical analysis to avoid deficiencies or excesses of fertilizers in maize cultivation, with the aim of increasing yields. Information was gathered from current documents, research articles, virtual libraries, and websites to present various opinions and ideas. The results show that soil chemical analysis offers essential benefits for maize fertilization, allowing for precise determination of nutritional needs and optimizing fertilizer use. There are various methods to analyze soil quality, each with its own utility and focus. Among the most common is chemical analysis, which measures concentrations of essential nutrients such as nitrogen, phosphorus, and potassium, as well as pH and organic matter. The chemical properties of the soil are fundamental for increasing maize crop production. The concentration of essential nutrients, such as nitrogen, phosphorus, and potassium, directly influences plant growth and development. The conclusions emphasize that soil chemical analysis is crucial for optimizing fertilization in maize cultivation, as it allows for the identification of nutrient deficiencies and excesses. The variety of methods for analyzing soil quality, which includes physical, chemical, and biological techniques, provides a comprehensive view of its state and fertility. The chemical properties of the soil, such as pH, cation exchange capacity, and nutrient content, are crucial determinants for maize growth and yield.